Risk factors associated with chronic obstructive pulmonary disease early readmission. (February 2014) - Lin, Jian; Xu, Youzu; Wu, Xiaomai; Chen, Meifang; Lin, Ling; Gong, Liuyang; Feng, Jiaxi
Abstract Background: The 31 day readmission rate is deemed to be an important indicator of the quality of medical care in China. The objectives of this study were to identify the readmission rate of acute exacerbation for chronic obstructive pulmonary disease (COPD) and to evaluate associated risk factors. Methods: We retrospectively reviewed charts for patients with acute exacerbation of COPD (AECOPD) admitted to our hospital between January 2011 and November 2012. The early-readmission group and non-early-readmission group were determined by whether patients were readmitted within 31 days after discharge. Logistic regression analysis was performed to identify risk factors for early readmission following an AECOPD. Results: There were 692 patients with 925 admissions during the 23 month period; 63 (6.8%) admissions met our criteria for early readmission. Multivariate analysis showed that chronic cor pulmonale (odds ratio [OR] 2.14, 95% confidence interval [CI] 1.26–3.64, p = 0.005), hypoproteinemia (OR 2.02, 95% CI 1.03–3.95, p = 0.040) and an elevated PaCO2 (OR 1.03, 95% CI 1.00–1.06, p = 0.027) were identified as risk factors for early readmission of AECOPD. Conclusion: The readmission rate for AECOPD was 6.8%. AECOPD patients with chronic cor pulmonale, hypoproteinemia, and a high PaCO2 are at higher risk for readmission with 31 days of hospital discharge, and medical care of these patients warrants greater attention.